Efectividad de un programa educativo en el conocimiento materno sobre cuidado del recién nacido prematuro - Ramos Cortegana, Elsa Violeta (2019)
The quantitative research of pre-experimental type pretest and posttest design was applied in the intensive care unit of neonatology Cajamarca Regional Hospital during the months of April to May 2016; in order to determine the fectiveness of the educational program in maternal knowledge about newborn care premature. The population consisted of 20 mothers who met the inclusion criteria. The survey was to determine the level of knowledge about maternal care in premature prepared by Celestino and Guevara for data collection; modified by the author. The obtained information is presented in sinple tables and double entry. For statistical analysis statistical test was used Cronbach’s alpha. The conclusions reached were: prior to the implementation of the educational program, 20 percent of mothers obtained a high level of knowledge, 70 percent of mothers earned an average level of knowledge and 10 percent of mothers received a low level of knowledge. After applying the educational program, 95 porcent of mothers obtained a high level of knowledge and 5 percent of mothers earned an average level of knowledge. The educational program was effective in improving the level of knowledge of mothers of preterm infants, yielding a value of -15,937 with probability 0.000 being highly significant.